Analisis Ekspresi Gen Selenometil Transferase pada Isolat Bakteri Termofilik Geobacillus 20K dan Thermomicrobium 14Ka sebagai Sumber Selenoprotein - Triana, Evi; Nurhidayat, Novik; Rahayu, Sri Hartin (Universitas Atma Jaya Yogyakarta, 2009)
Selenium is a trace element that has essential nutrition value for human. Besides its nutritional value, it has important health benefits, including being a cancer chemoprotective agent. Methylated form of selenium is the most effective compound against cancer cells. Selenomethyl transferase (SMT) is responsible for methylating of selenium. This enzyme is coded by selenomethyl transferase (smt) gene which was found only from selenium accumulator plant, Astragalus bisulcatus. Thermophilic bacteria Thermomicrobium 14Ka and Geobacillus 20K have ability to accumulate selenium as well and potential in fighting cancer cells. Therefore a study to determine smt gene and its expression in both bacteria had been conducted in order to develop natural product of seleno-metilselenosistein for cancer treatment. The result showed that Thermomicrobium 14Ka and Geobacillus 20K have putative smt (selenomethyl transferase) gene, and such gene was expressed at different intensity. Geobacillus 20k expressed smt gene at higher intensity than Thermomicrobium 14k. Therefore, it is presumable that Geobacillus has a significant role in cancer remedy, meanwhile Thermomicrobium plays an essential role as cancer protective agent.